2004
DOI: 10.1007/s00441-004-0991-6
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular vesicular aggregations of GABAB R1a and R1b receptors increase with age in neurons of the developing mouse brain

Abstract: GABA(B) receptors play a critical neuromodulatory role in the central nervous system. It has been suggested that both the functional role and the cellular distribution of GABA(B) receptors in the neuronal network change during post-natal maturation. In the present study, the cellular and subcellular distribution patterns of the GABA(B) R1a/b receptors have been analysed in different brain regions of the mouse using immunocytochemistry with isoform-specific antisera. GABA(B) R1-immunoreactivity (IR) was present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Further heterogeneity could be predicted from putative interactions involving the extracellular "sushi domains" (59) or formation of intracellular complexes between GABA A R-␥2S and GABA B R1 (60) or RGS-mediated binding to coupled GIRK channels (61). The striking "vesicular" appearance of the GABA B R staining pattern, previously described in neurons (62) and Schwann cells (27), is consistent with the existence of multiprotein GABA B R2-containing complexes.…”
Section: Discussion Mesc and Gabar Expressionsupporting
confidence: 58%
“…Further heterogeneity could be predicted from putative interactions involving the extracellular "sushi domains" (59) or formation of intracellular complexes between GABA A R-␥2S and GABA B R1 (60) or RGS-mediated binding to coupled GIRK channels (61). The striking "vesicular" appearance of the GABA B R staining pattern, previously described in neurons (62) and Schwann cells (27), is consistent with the existence of multiprotein GABA B R2-containing complexes.…”
Section: Discussion Mesc and Gabar Expressionsupporting
confidence: 58%
“…GABA-B 1 receptor subunits, which remain in the endoplasmic reticulum (ER) in the absence of GABA-B 2 subunits (102105). However, the distribution of GABA-B 1 in the central nervous system is much broader than that of GABA-B 2 , which suggests that this receptor may have an independent function intracellularly (106108). It was demonstrated that a recently deorphanized GPCR, GPR30, targeted exclusively to the ER, is a functional receptor for estrogen (109).…”
Section: Gβγ Subunits and Effectors Localized At Sites Distinct From mentioning
confidence: 99%
“…Funcional GABA B receptors are present in pre-Bötzinger complex of neonatal mice GABA B receptors have been shown to be expressed (Lopez-Bendito et al, 2002;Ritter et al, 2005) and functional (Zhang et al, 2002) at early stages of development.…”
Section: 1mentioning
confidence: 99%